Gastroprotective Effect of Anisomeles indica on Aspirin-Induced Gastric Ulcer in Mice - Hsiu-Man Lien; Yu-Yen Wang; Mei-Zi Huang; Hui-Yu Wu; Chao-Lu Huang; Chia-Chi Chen; Shao-Wen Hung; Chia-Chang Chen; Cheng-Hsun Chiu; Chih-Ho Lai (MDPI AG, 2022)
Gastric ulcers are commonly seen in the upper gastrointestinal tract and may be related to the Helicobacter pylori infection and the use of aspirin, a nonsteroidal anti-inflammatory drug (NSAID). Typically, proton-pump inhibitors (PPIs) are used to treat gastric ulcers; however, adverse effects have emerged following long-term treatment. Natural medicines are used as alternative therapeutic agents in the treatment of gastric ulcers, with few side effects. Despite various reports on the anti-H. pylori and anti-gastric cancer activities of Anisomeles indica, its gastroprotective effect on ulcers remains undetermined. This study investigated the protective effect of A. indica on aspirin-induced gastric ulcers in murine models. Our results show that three fractions of ethanol-extracted A. indica inhibited aspirin-induced gastric injury. Among these, A. indica Fraction 1 was observed to enrich ovatodiolide, which effectively diminished gastric acidity and alleviated aspirin-induced inflammation in the stomach. Our results provide evidence that A. indica could be developed as an effective therapeutic agent for gastroprotective purposes.